Imagen y realidad del cuerpo en el mundo de hoy - Hevia Garrido Lecca, Julio (2003)
This essay will be about a set of practices and tendencies that govern the image and reality of bodies. Generally, we will characterize what it is called today light culture, as well as the different regimes taken by those who try, obsessively, to emphasize figure and make out of their own autonomy an strong credential in daily interchange. This set of variables will be tied to bulimia and anorexia problems, which, aside from being considered as pathologies more o less generalized among young people, are extremes signals of an style of life, which can oscillate between an strong consumerism and restricted needs systematically applied.